IMPACT OF INTERRUPTION: LITERACY INSTRUCTION DURING THE COVID-19 PANDEMIC - (:unkn) unknown (My University, 2024)
The COVID-19 pandemic significantly disrupted traditional education, necessitating a rapid shift to online and hybrid teaching models. This study initially aimed to investigate the impact of these changes on elementary literacy instruction. However, the findings predominantly reflect the broader experiences of teachers adapting their methodologies for remote learning during the pandemic. Grounded in the sociocultural theories of Vygotsky and Gee, this study how the shift to digital platforms influenced teaching practices, including literacy.The research employs a qualitative design, utilizing semi-structured interviews with ten elementary educators from various public and charter schools across the United States. These educators provided in-depth insights into the challenges and adaptations required for effective teaching during the pandemic. The participants' narratives revealed a broader focus on their overall teaching experiences and crisis management strategies. Key findings highlight significant challenges in maintaining student engagement and accurately assessing student development in an online environment. Although the integration of digital tools, flexible teaching methods, and culturally relevant pedagogies were discussed, they were often viewed as additional burdens rather than central strategies. The study revealed the complexity and resilience required of educators during this period, underscoring the importance of support systems for teachers. This study contributes to the broader understanding of teaching in crisis contexts, emphasizing the need for flexible, adaptive teaching approaches that can accommodate diverse learner needs. The critical role of technology in contemporary education is underscored, as well as the necessity for systemic support to aid educators in navigating unprecedented challenges. Insights from this study aim to inform best practices for teaching in online and hybrid learning environments, ensuring educators are better prepared for future educational disruptions.
Keywords: COVID-19 Pandemic; Crisis Education; Literacy Instruction; Qualitative Research; Remote Education; Teacher Perspectives